Pietrini Daniela, La lingua infetta. L’italiano della pandemia (Altre Modernità, 2022)
Pietrini Daniela, La lingua infetta. L’italiano della pandemia (Roma, Treccani, 2021, 240 pp. ISBN 978-881-200-890-2)di Roberto Laghi